The Testosterone-Derived Neurosteroid Androstanediol Is a Positive Allosteric Modulator of GABA(A) Receptors - Reddy, Doodipala Samba (The American Society for Pharmacology and Experimental Therapeutics, 2010)
Testosterone modulates seizure susceptibility, but the underlying mechanisms are obscure. Recently, we demonstrated that testosterone affects seizure activity via its conversion to neurosteroids in the brain. Androstanediol (5α-androstan-3α,17β-diol) is an endogenous neurosteroid synthesized from testosterone. However, the molecular mechanism underlying the seizure protection activity of androstanediol remains unclear. Here, we show that androstanediol has positive allosteric activity as a GABA(A) receptor modulator. In whole-cell recordings from acutely dissociated hippocampus CA1 pyramidal cells, androstanediol (but not its 3β-epimer) produced a concentration-dependent enhancement of GABA-activated currents (EC(50) of 5 μM). At 1 μM, androstanediol produced a 50% potentiation of GABA responses. In the absence of GABA, androstanediol has moderate direct effects on GABA(A) receptor-mediated currents at high concentrations. Systemic doses of androstanediol (5–100 mg/kg), but not its 3β-epimer, caused dose-dependent suppression of behavioral and electrographic seizures in mouse hippocampus kindling, which is a model of temporal lobe epilepsy. The ED(50) value for antiseizure effects of androstanediol was 50 mg/kg, which did not produce sedation/motor toxicity. At high (2× ED(50)) doses, androstanediol produced complete seizure protection that lasted for up to 3 h after injection. The estimated plasma concentrations of androstanediol producing 50% seizure protection in the kindling model (10.6 μM) are within the range of concentrations that modulate GABA(A) receptors. These studies suggest that androstanediol could be a neurosteroid mediator of testosterone actions on neuronal excitability and seizure susceptibility via its activity as a GABA(A) receptor modulator and that androstanediol may play a key role in men with epilepsy, especially during the age-related decline in androgen levels.